Fragmentos de uma sociabilidade emergente: a trajetória do Núcleo do Trabalho do Programa de Saúde Mental de Santos (1989-1996) - Kinker, Fernando Sfair (2011)
The object of this paper is to present the experience developed on Nucleus of Work of the Mental Health Program of Santos from 1989 to 1996. The goal is to make a reflection on the emergence of new forms of sociability, starting from the criticism and deconstruction of the modern sociability, centered on labor and goods, beside the criticism of the psychiatric paradigm. This study is composed by interposed fragments of text, that comprehend the following topics: description of the labor project s characteristics and the overcome of the traditional labor-therapeutic practices; elements of the moderns work geneses; description of the experiences lived with the users-workers of the labor project; reflection on the modern forms of sociability, focused on labor and goods; description of scenes from the work of Nucleus of Work team. Through references that approach the theoretical perspective of deinstitutionalization and complexity, valorizing the significance of experience and daily life concepts, this study defends the thesis that the deconstruction of the conventional psychiatric paradigm leads to the deconstruction of the kind of sociability centered on labor and commodity, requiring the construction of new emerging forms of sociability that produce life and are focused on the direct communication between people, besides new ways of interaction with objects and nature.